2008
DOI: 10.1243/09544100jaero347
|View full text |Cite
|
Sign up to set email alerts
|

Novel chevron nozzle concepts for jet noise reduction

Abstract: Chevron nozzles are known to be excellent attenuators of jet noise. Conventional chevron nozzles use triangular serrations at the trailing edge of the nozzle. This article proposes two novel chevron concepts and evaluates their noise reduction performance. The new chevron concepts proposed are protrusions with a sinusoidal profile and chevrons with asymmetry. These nozzles are compared against the symmetric chevron nozzle with triangular profile and a baseline circular nozzle without chevrons. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To investigate the effect of the chevron profile (curvature along the azimuthal direction) on the far-field noise, Tide and Srinivasan [5] have performed experiments on various chevron nozzles for a wide range of Mach numbers. They compared the sinusoidal profile chevron nozzle with the conventional chevron nozzle, which has a linear profile.…”
mentioning
confidence: 99%
“…To investigate the effect of the chevron profile (curvature along the azimuthal direction) on the far-field noise, Tide and Srinivasan [5] have performed experiments on various chevron nozzles for a wide range of Mach numbers. They compared the sinusoidal profile chevron nozzle with the conventional chevron nozzle, which has a linear profile.…”
mentioning
confidence: 99%
“…Drastic modification of the jet cross-section was achieved by the investigated configurations, with both elliptic and triangular shapes attained downstream. Consequently, screech was nearly eliminated with reductions in the range of [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] dB depending on the operating condition. Analysis of the streamwise velocity indicated that both the mean shock spacing and strength were reduced resulting in an increase in the broadband shock associated noise spectral peak frequency and a reduction in the amplitude, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, of the above mentioned studies, Seiner et al [1] was the only group which did not employ 12 chevrons and only a single chevron configuration was investigated. Arrangement has been investigated in the past for chevrons applied to non-military style nozzles in both subsonic [9], and supersonic [10][11][12] jets. Bridges and Brown [9] found that periodic azimuthally spaced chevrons with asymmetric geometry were detrimental to subsonic noise reduction when compared to chevrons with symmetric geometry and identical penetration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, examination of the relationships between chevron geometric parameters and flow characteristics was performed. Tide and Srinivasan [19] proposed two novel chevron concepts and evaluates their noise reduction performance. The new chevron concepts proposed were protrusions with a sinusoidal profile and chevrons with asymmetry.…”
Section: Introductionmentioning
confidence: 99%